Walter Camp and the Creation of American Football - Tamte, Roger R., 1935- (Book collections on Project MUSE., 2018)
"No person was more responsible for converting English rugby into American football than Walter Camp (1859-1925). As a player at Yale, then a coach at Yale and Stanford, a sportswriter for Harper's Weekly and other major magazines, and an influential member of rules committees, he patiently and gradually transformed the sport into the football we recognize today. In this freshly researched biography, Roger Tamte follows Camp from infancy to the meeting of the rules committee in 1903. That meeting established the modern game, including scoring, play ending after a tackle, resuming on opposite sides of a line of scrimmage, plays beginning with a snap to the quarterback, and a system of downs and yardage goals for retaining or losing possession. The incremental changes that Camp introduced and championed did not come easily. In addition to the usual resistance to change, he had to confront academic, press, and governmental complaints about the brutality of the game. As the popularity of college football drew more spectators, games needed larger stadiums. Camp had to address questions of eligibility, officiating, and scheduling. And he had a personal life and a professional business career to maintain. His was a busy life, and one worth telling"--